The strategies of guidance and counseling teachers to increasing students’ moral awareness in senior high school - Purwasih, Retno; Sanyata, Sigit; Retnawati, Heri (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2020)
Moral awareness is a condition where the individual understands and comprehends the actions taken, both in the past, present, and future and realizes how the impact of behavior carried out both for oneself, others, and the surrounding. The purpose of this study is to find out how is the strategies of guidance and counseling teacher to increasing the moral awareness of students so far. This research is a qualitative type of phenomenology research. The data were collected through observation and interviews. The participants of the interviews were guidance and counseling teachers who teach in high schools which were chosen randomly. The data which were obtained from interviews were analyzed using the Miles & Huberman qualitative research model. The results showed the guidance and counseling teachers’ strategies in increasing moral awareness mostly through group guidance, group counseling, individual counseling, and responsive services with lecturing method, discussion, short film, and modeling.